2016
DOI: 10.1111/jerd.12230
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Diode Laser and Gluma on Post‐Preparation Sensitivity: A Randomized Split‐Mouth Clinical Study

Abstract: The application of Gluma or a 940-nm diode laser may be considered as effective in reducing sensitivity after tooth preparation without superiority of either method. (J Esthet Restor Dent 28:405-411, 2016).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…Mechanism of desensitizer is by the way of occluding or sealing of dentin tubules. 1,2 Several treatment methods such as tubular obturating and surface covering procedures, adhesives, anti-inflammatory agents, and lasers may be applied to the sensitive surface after tooth preparation. 3 A durable cementation is crucial for long-term restoration survival, marginal sealing, and strong adhesion.…”
Section: Introductionmentioning
confidence: 99%
“…Mechanism of desensitizer is by the way of occluding or sealing of dentin tubules. 1,2 Several treatment methods such as tubular obturating and surface covering procedures, adhesives, anti-inflammatory agents, and lasers may be applied to the sensitive surface after tooth preparation. 3 A durable cementation is crucial for long-term restoration survival, marginal sealing, and strong adhesion.…”
Section: Introductionmentioning
confidence: 99%
“…Kara et al 30 in a clinical study, separately compared the efficacy of the 940 nm diode laser and Gluma for the treatment of DH following tooth preparation. They indicated that none of the tested modalities had any superiority over the other.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, a direct comparison cannot be done. Kara et al 22 have evaluated the effect of the gluma and diode laser on postoperative sensitivity. They reported a significant reduction in post-preparation sensitivity level in both groups when compared with the control.…”
Section: Discussionmentioning
confidence: 99%